Living World in a Box. - Kushner, David
Dave Jones, entrepreneurial game designer known for Grand Theft Auto and Lemmings, talks about getting beat up by Scottish gangs as a kid for achieving a high score in Galaga, how GTA originally had dinosaurs roaming its city streets, and his upcoming game, All Points Bulletin.
Keywords: Grand Theft Auto games; Lemmings (Game); Video games; Internet games; Jones, Dave